Transformation from Business to Personal Strategy with a Focus on Retirement - Jehiel Zif (Journal of Management Research, 2024)
The paper outlines a transformation of various concepts from business to personal strategy with a focus on retirement: type of strategy, multiple objectives, product life cycle and prediction, strategy development, direction and concentration of effort, strategy implementation and performance evaluation, change readiness and corrective action. We propose that conceiving together a personal strategy and change readiness is a logical way to combine deliberate planning with flexible tuning to unanticipated events. In similarity to business, multiple objectives are essential for achieving life satisfaction. Priority among these objectives needs to be modified according to retirement life stages, which are reviewed. The paper presents an approach to assessing the decision to concentrate on various life satisfaction objectives versus enjoyment in the here and now. Three stages of change readiness with adaptation to retirement situations are outlined: trigger identification, preparation for action, and mode of action. Even with high inertia at an advanced age, it is better to change before one has to, and the paper offers some insight about the way this can be accomplished. Recent research publications on longevity and happiness point to the value of planning and the role of relationships. These findings fit the strategic approach to retirement. In conclusion, we support the notion that life satisfaction, happiness, and longevity are determined more by plan than by luck.